Stacking geometry between two sheared Watson-Crick basepairs: Computational chemistry and bioinformatics based prediction - Maiti, Satyabrata; Mukherjee, Debasish; Roy, Parthajit; Chakrabarti, Jaydeb; Bhattacharyya, Dhananjay (Biochimica et biophysica acta. General subjects, 2020)
Molecular modeling of RNA double helices is possible using most probable values of basepair parameters obtained from crystal structure database. The A:A w:wC non-canonical basepair, involving Watson-Crick edges of two Adenines in cis orientation, appears quite frequently in database. Bimodal distribution of its Shear, due to two different H-bonding schemes, introduces the confusion in assigning most the probable value. Its effect is pronounced when the A:A w:wC basepair stacks on Sheared wobble G:U W:WC basepairs. We employed molecular dynamics simulations of three possible double helices with GAG, UAG and GAU sequence motifs at their centers and quantum chemical calculation for non-canonical A:A w:wC basepair stacked on G:U W:WC basepair. We noticed stable structures of GAG motif with specifically negative Shear of the A:A basepair but stabilities of the other motifs were not found with A:A w:wC basepairing. Hybrid DFT-D and MP2 stacking energy analyses on dinucleotide step sequences, A:A w:wC::G:U W:WC and A:A w:wC::U:G W:WC reveal that viable orientation of A:A::G:U prefers one of the H-bonding modes with negative Shear, supported by crystal structure database. The A:A::U:G dinucleotide, however, prefers structure with only positive Shear. The quantum chemical calculations explain why MD simulations of GAG sequence motif only appear stable. In the cases of the GAU and UAG motifs “tug of war” situation between positive and negative Shears of A:A w:wC basepair induces conformational plasticity. We have projected comprehensive reason behind the promiscuous nature of A:A w:wC basepair which brings occasional structural plasticity. •We used bioinformatics and MD simulation to predict structure of GAG.UAU sequence formed by sheared AA and GU basepairs.•Prediction of structures of UAG.UAG and GAU.GAU sequence motifs using same protocol reveal structural disorders.•Stacking energy analyses of A:A w:wC::G:U W:WC and A:A w:wC::U:G W:WC dinucleotide have been done using quantum chemistry.•The quantum chemical calculations prove the reason behind stability as well as conformational plasticity.